HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN AKURASI SMASH JUMP DALAM PERMAINAN BULU TANGKIS PADA CLUB PUTRA PB. BINA PRESTASI KAMPAR UTARA KABUPATEN KAMPAR - Irwan Hadi Hadi; Ramadi '; Ardiah Juita Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The research problem is still the lack of accuracy in the club men’s jump smash PB.Bina prestasi kampar utara kabupaten kampar. The predicted shortage of leg muscle explosive power that influence . this study aimed to examine the relationship explosive leg muscle power with accuracy in a game of badminton jump smash in the club son PB.Bina prestasi kampar utara kabupaten kampar. This study is correlational is to determine whether the relationship between variables. The population in this study was the son of club athletes PB.Bina prestasi kampar utara kabupaten kampar, seventeeen  sons who carried on the men’s club PB.Bina prestasi kampar utara kabupaten kampar by using the total sampling. Research instrumens explosive leg muscle power ( jump vartical ), while the accuracy of the jump smash, the main usefulnes of this test is to measure the accuracy of smash. The data obtained were analyzed using product moment correlation. Before the data were analyzed first tested for normality with liliefors test. Observation liliefors maxsimum value max denoted L0, where L0 value max < l table the samples come from normally distributed populations. L0 max on leg muscle explosive power count obtained for = 0.1667 then L0 max on the accuracy of the results obtained for a jump smash = 0.1439 and table l obtained = 0,206 Furthemore, to determine the extent to which the relationship between leg muscle explosive power to jump on the club smash accurasy son PB.Bina prestasi kampar utara kabupaten kampar count calculate obtained r = 0,179 and table r = 0,482 then obtained count calculate r = 0.179 < table r = 0.428 at a = 0,05. So thus Ho accapted Ha rejected. So there is no relationship between the explosive power disignifikan leg muscle with a jump smash accurasy. Keywords :Explosive leg muscle power, accuracy jump smash